The Brexit Vote and The Trump Vote: A comparative study of the common trends and factors that led to a populist radical right vote in Britain and the United States - Laëtitia Langlois (Revue LISA)
The two symbols of Western liberal democracies – Britain and the US – became in 2016 hotbeds of radical right populism. The vote for Brexit and Donald Trump’s election represent two spectacular populist victories and this article will highlight the strikingly similar dynamics at work in both elections. We will see that the two populist leaders, Nigel Farage in Britain and Donald Trump in the US, mobilised the same arguments and themes to connect to an audience which for years had nourished resentment and anger at the way traditional politicians had governed national politics in their respective countries. Thus, with the Brexit and Trump victories, fringe narratives became mainstream politics and upset the established political order. Nativism, racism and xenophobia, anti-establishment attitudes became the dominant themes of the political debate. It is important to understand how two major Western democracies surrendered to the populist calls and this article tries to provide an analysis on this populist phenomenon in Britain and the US.